Pengaruh Teknologi Digital Terhadap Kebiasaan Dan Pola Perkembangan Generasi Alpha - Sopiyan Apandi; Ayu Talenta Lumbantoruan; Medina Fikanti; Kartika Nazawa Sri Utami; Siti Fatul Zahrani (Departement of Mathematics Education, 2025)
Generation Alpha is a group of generations born after 2010 and grow up in a digital era dominated by technological advances. This article aims to analyze the influence of digital technology on the habits and development patterns of this generation. The research method used is literature study and descriptive analysis. The results show that digital technology has a significant impact on the learning patterns, social interactions and cognitive development of the Alpha generation. On the one hand, technology supports digital-based learning, creativity development, and access to unlimited information. However, the challenges of technology a addiction, reduced face-to-face social interaction, and mental health issues must also be addressed. This study recommends managing the use of digital technology wisely by parents and educational institutions to maximize benefits and minimize negative impacts.